It's good to talk: dialogue between strategic environmental assessment and plan-making. Issue 1 (January 2019) - Hayes, Samuel
Abstract : Literature provides a basis for understanding the relationship between strategic environmental assessment (SEA) and plan-making. This research furthers this by examining dialogue between SEA and plan-making more closely. The research draws on communicative planning, SEA paradigm shifts and theories of power. Four case studies from Scotland and England are analysed via interviews and documentary evidence. It is found that dialogue is constrained by tiered plan-making, pre-existing commitments and political context. Capabilities to enable dialogue can be supported by iteration in SEA and plan-making, and governance structures that bring practitioners together. Contradictions in epistemology are also found to potentially curtail dialogue.